MR Imaging Spectrum of Neuro Rhino Sino Orbital Fungal Infections in patients treated for COVID - Kachewar, Sushil Ghanshyam; Kachewar, Smita (Nepal Journal of Neuroscience, 2021)
Objectives: To analyse the spectrum of imaging findings of fungal infection as seen in MRI images of priorly treated for COVID. Materials and methods: The different patterns of findings of Neuro Rhino Sino Orbital Fungal Infections as seen in MRI images in 100 patients who received standard treatment for COVID in recent past and presented with suggestive signs and symptoms. Results: No positive MRI findings to suggest any neural tissue, orbital or Sino nasal involvement was seen in 35 % of cases. Only sino nasal involvement noted in 23 % cases. Sino-nasal as well as orbital involvement seen in 21 % cases. Neuro Sino Naso Orbital lesions were seen in 11% cases. Non fungal orbito-facial soft tissue inflammation was seen in 10 % cases. Conclusion: In patients who have received standard treatment for Covid and who later developed signs and symptoms of neural, orbital or Sino nasal involvement; positive imaging findings were noted in 65% cases. Fungal infections were seen more in middle aged population [40-60 years of age]. About 75 % of affected patients were known diabetics. Neural involvement was least common. This study proposes a new staging system [Stage 0, X, I, II, III, IV] for describing the affected region by fungal infection.